Diagnostic accuracy of diffusion tensor magnetic resonance imaging in differentiating between high-grade and low-grade partial anterior cruciate ligament tear - Sheng, Chua Yen (2023)
Introduction: Anterior cruciate ligament (ACL) tear is the most common knee ligament injury encountered in radiology and orthopedic practice. Magnetic Resonance Imaging (MRI) findings of ACL injury are categorized as intact, partial tear or complete tear. Partial ACL tear should be further classified into high-grade and low-grade partial tear, which provides useful information regarding the necessity of surgical reconstruction. Diffusion tensor imaging (DTI) with fiber tractography is a new technique which can be utilized for quantitative and qualitative assessment in differentiating high-grade and low-grade partial ACL tear as well as overall grading of ACL injury. Methodology: A total of 260 patients aged 16 to 45 years old with suspected traumatic ACL injury were enrolled in this study, which include a study group of 96 patients who underwent MRI knee examination using combined DTI and conventional sequences, and another control group of 164 patients who underwent MRI knee examination using only conventional sequences. DTI sequence was performed using b-values of 0s/mm2 400 s/mm2 and 800s/mm2, and 32 diffusion-encoding directions. During post-processing of DTI studies, four quantitative parameters were derived, namely fractional anisotropy (FA), apparent diffusion coefficient (ADC), axial diffusivity (AD) and radial diffusivity (RD). In addition, diffusion tensor tractography was generated for qualitative assessment of ACL injury. The MRI findings of ACL were categorized into 4 groups, which include intact (grade 0), low-grade partial tear (grade I), high-grade partial tear (grade II) and complete tear (grade III). The cut-off values of FA and ADC used in differentiating high-grade from low-grade ACL injuries are ≤0.348 and ≥2.400 x 10-3mm2/s, respectively. The MRI grading of ACL injury was compared to arthroscopic findings as the diagnostic reference standard. Statistical analysis was performed to analyze and compare the diagnostic accuracy between the study group and the control group. Results: The study group of patients who underwent MRI knee examination using combined DTI and conventional sequences demonstrated higher diagnostic accuracy in differentiating high-grade and low-grade partial ACL tear (86.4% sensitivity and 82.4% specificity) in comparison to the control group of patients who underwent MRI knee examination using only conventional sequences to differentiate high-grade and low-grade partial ACL tear (70.6% sensitivity and 68.4% specificity). FA values are negatively correlated with the severity of ACL injury (r=-0.857, P<0.01) while ADC, AD and RD values are positively correlated with the severity of ACL injury (r=0.899, P<0.01; r=0.689, P<0.01; and r= 0.731, P<0.01, respectively). Conclusion: DTI with fiber tractography can provide useful additional information for both quantitative and qualitative assessment of ACL injury to improve diagnostic accuracy. Therefore, DTI sequence should be used in combination with conventional sequences in MRI examination of traumatic knee injury for suspected ACL tear.